1974
DOI: 10.1002/eji.1830040205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of normal mouse serum on mouse lymphocyte transformation in vitro

Abstract: Mouse spleen cells were cultured in the presence or absence of one of the following mitogens: phytohemagglutinin (PHA), concanavalin A, allogeneic spleen cells or bacterial lipopolysaccharide. The addition of normal mouse serum (NMS) to the cultures usually depressed mitogen-induced lymphocyte transformation as measured by DNA, RNA o r protein synthesis, whether calculated as gross o r net synthesis. The degree of depression was increased as the concentration of NMS serum increased. DNA and RNA synthesis in un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…data]. Different opinions concerning the effect of NMS on the mixed lymphocyte reaction have been published earlier [13,16]. However, these authors mainly used different serum concentrations, and if these discrepancies are taken into ac count, the results could be compatible with each other.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…data]. Different opinions concerning the effect of NMS on the mixed lymphocyte reaction have been published earlier [13,16]. However, these authors mainly used different serum concentrations, and if these discrepancies are taken into ac count, the results could be compatible with each other.…”
Section: Discussionsupporting
confidence: 62%
“…No conclusive evidence for the effect was obtained [3,4], The result of addition of autologous mouse serum to lymphocytes stimulated by polyclonal T cell activators, such as concanavalin A, as well as to poly clonal B cell activators (PBA), as measured by 3H-thymidine incorporation, has also been studied. It has been shown that concanavalin A, phytohemagglutinin and lipo polysaccharide (LPS)-induced increase in DNA synthesis is diminished, when lympho cytes are cultured with NMS [13]. It has also been reported that the polyclonal acti vation of plaque-forming cells (PFC) by fe tal calf serum is inhibited by syngeneic mouse serum [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background activity of NMS can partly be ascribed to the presence of minor amounts of TNF (Shah, Green & Moore, 1978;Green, Chiasson & Shah, 1979) and partly to another factor shown to inhibit DNA synthesis by mouse lymphocytes (Nelson & Shneider, 1974;Smith & HammarstrOm, 1979). This factor shares some physicochemical characteristics with TNF such as its nondialysable glycoprotein nature, its heat-stability (30 min, 56°C) and its electrophoretic mobility as an a-globulin (Nelson & Shneider, 1974;Green, Dobrjansky, Carswell, Kassel, Old, Fiore & Schwartz, 1976). TNF, however, has another elution pattern on Sephadex G20 o (Green et al, 1976) and unlike the other inhibitory factor (Nelson, 1972), cannot be demonstrated nor induced in serum of nude mice (Hoffmann, Oettgen, Old, Mittler & Hammerling, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Norway). The discs were counted with PPO-PO POP-toluene scintillant as described elsewhere (Nelson and Shneider, 1974). The results are shown as arithmetical mean counts per minute (c.p.m.)…”
Section: Lymphocyte Culturesmentioning
confidence: 99%